SITUS KESUBEN: SUATU BUKTI PERADABAN HINDU-BUDDHA DI PANTAI UTARA JAWA TENGAH - Sukawati Susetyo (KALPATARU, 2015)
The Indonesian Ancient History has recorded that the oldest historical period in Central Java was the period of the Ancient Matarām Kingdom (8th – 10th centuries CE). At the same period there was the kingdom of Srivijaya on the east coast of Sumatera. On the other hand, according to Chinese chronicles, there had been a kingdom in Java in 5th century CE, namely Ho-ling (She-po). Recent investigations along the north coast of West Java and the east coast of Sumatera have yielded evidences of relations between Indonesia and foreign countries in forms of imported artifacts, although this is not supported by inscriptions. This indicates that evidences of international relations have to be searched in coastal areas because it was where the relations began. The research on the north coast of Central Java was carried out in forms of survey, excavation, and thorough interviews, and the writing method is descriptive-comparative. This research has provided new evidence in form of a candi (temple) at Kesuben Village in Lebaksiu District, Tegal Regency, Central Java. The finds include structure of candi made of bricks, antefixes, and stone statues. Unfortunately we have not been able to identify the religious background of the Candi Kesuben (Kesuben Temple) because there has not been any artifact that can support the identification. Sejarah kuno Indonesia mencatat bahwa masa sejarah tertua di Jawa Tengah adalah Kerajaan Matarām Kuno (abad ke-8-10). Pada waktu yang sama di pantai timur Sumatera terdapat Kerajaan Sriwijaya. Di lain pihak, berita Cina menginformasikan bahwa kerajaan di Jawa sudah ada pada abad ke-5, yaitu Ho-ling (She-po). Penelitian mutakhir di pesisir pantai utara Jawa Barat dan timur Sumatera memberikan bukti adanya hubungan antara Indonesia dengan bangsa asing berupa artefak-artefak dari luar negeri, meskipun tidak didukung oleh data prasasti. Hal tersebut memberikan petunjuk untuk mencari bukti awal hubungan dengan bangsa lain di daerah pesisir pantai. Penelitian di pesisir pantai utara Jawa Tengah ini dilakukan dengan survei, ekskavasi, dan wawancara mendalam, metode penulisan menggunakan metode deskriptif komparatif. Penelitian ini berhasil menambahkan data baru berupa temuan candi di Desa Kesuben, Kecamatan Lebaksiu, Kabupaten Tegal, Jawa Tengah.Temuan yang dihasilkan berupa struktur bangunan candi dari bata, antefiks-antefiks, dan arca batu. Hingga saat ini dari penelitian ini belum diketahui latar keagamaan Candi Kesuben karena belum ditemukan artefak yang mendukung.